Audio Visual Education To Prevent Fall Risk For Patients' Family In The Icu Of Hospital - Aprin Rusmawati; Suyanto; Alfian Fawzi (Master of Public Health Program Universitas STRADA Indonesia, 2026)
Knowledge about fall risk prevention is very much needed by the patient's family, one of which is through audio visual education on fall risk prevention. This study aims to determine the effect of audiovisual education on fall risk prevention in the ICU of Hospital. This research method uses a Preexperimental with One Group Pretest-Posttest Design with 28 respondents. The sample determination used a purposive sampling technique. The independent variable in this study is audiovisual education, while the dependent variable in this study is knowledge of fall risk prevention. Data analysis used the Paired T-Test. There is significant increase in knowledge was obtained before and after audiovisual education was conducted on respondents, there was an increase from 3.11 to 6.96 and an increase in knowledge of 57.1% from 1 (3.6%) person to 17 (60.7%) person. Based on the results of the Paired T-test statistical test, the Sig value was obtained. (2-tailed) = 0.000 which means that statistically there is an effect of audiovisual education on the prevention of the risk of falling on the patient's family in the ICU of Hospital. The audiovisual education method for preventing the risk of falls is an effective educational method for education with a result of an increase in knowledge.